Fisherman Boundary Detection Using Android - Kanniga, E.; Seetharam, N. (International Journal of Psychosocial Rehabilitation, 2019)
Nowadays fishermen facing lot of problem, during fishing they may be crossed the boundary from their country. Due to miscommunication and misunderstanding, to avoid this in this project will provide the solution to protect from hazards, this android app is more helpful for them. Cost wise also too low. By using the GPS we can detect the boundary area.